2002
DOI: 10.1034/j.1600-0897.2002.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Cyclooxygenase‐2 in Local Lesions of Endometriosis Patients

Abstract: Hyper activation of COX-2 with abnormal prostaglandin generation is considered to contribute to the pathophysiology of endometriosis and disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 24 publications
4
75
2
1
Order By: Relevance
“…It has been reported that COX-2 plays a role in endometriotic cell proliferation, survival, migration and invasion [9,15,16]. Chishima et al [17] showed increased expression of COX-2 in local lesions of endometriosis patients. They put forward that hyperactivation of COX-2 with abnormal PG production contributes to the pathophysiology of endometriosis and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that COX-2 plays a role in endometriotic cell proliferation, survival, migration and invasion [9,15,16]. Chishima et al [17] showed increased expression of COX-2 in local lesions of endometriosis patients. They put forward that hyperactivation of COX-2 with abnormal PG production contributes to the pathophysiology of endometriosis and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 is more abundantly expressed in ectopic endometria than in the eutopic endometria during similar phases of the menstrual cycle in women (Ota et al, 2001;Chishima et al, 2002). COX-2 is expressed in both glandular epithelium and stroma of endometriotic tissues in women (Ota et al, 2001;Chishima et al, 2002). Cytokines increase COX-2 expression in endometriotic stromal cells (Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Much of the endometriotic pain is thought to be due to high levels of PGE 2 (Allen et al, 2005). COX-2 is more abundantly expressed in ectopic endometria than in the eutopic endometria during similar phases of the menstrual cycle in women (Ota et al, 2001;Chishima et al, 2002). COX-2 is expressed in both glandular epithelium and stroma of endometriotic tissues in women (Ota et al, 2001;Chishima et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Since PGs are unstable factors with a very short halflife (Ferreira and Vane, 1967), it is believed they must be produced and function locally. Hence, peritoneal macrophages (Wu et al, 2002) and ectopic endometriotic tissue (Ota et al, 2001;Chishima et al, 2002Chishima et al, , 2007 are two of the most likely candidates implicated in raising peritoneal eicosanoid levels.…”
Section: Introductionmentioning
confidence: 99%